Response some plants to ionic toxicity of zinc and lead chloride - El-Mugrbi, Widad Saed; Entesar M. Ibrahim; Ahmed S. Ibrahim (Sebha University Conference Proceedings, 2025)
Environmental pollution is one of the major sources of health menace. heavy metals are considered more dangerous than other pollutions for the reason that heavy metals cannot be devastated by degradation. The present study was conducted to response of three plant species (Cucumber, Sun flower and Tomato) to ion toxicity of Zinc and Lead chloride salts. Used different concentrations of heavy metals (Zn and Pb) as impact on germination period and seedling development stages of target plant species. Results showed that, different levels of heavy metals (ZnCl2 and PbCl2) caused decrease of germination parameters of cucumber plant, while Shoot length and fresh weight of same plant were increased with increasing lead and zinc chloride levels as compared with control. Tomato plant was highly sensitive to different concentrations of lead and zinc chloride. Whereas, all germination parameters decrease with increased heavy metal treatments except germination percent and coefficient velocity of germination were increased especially at the levels at 1000 and 1500 ppm. Sun flower plant was more respond of heavy metal treatments, where, germination parameters (germination percent, mean germination time, mean daily germination and coefficient velocity of germination) were increased under these compounds. Different levels of lead and zinc chloride were enhanced dry weight of sun flower seedling especially at 1500 and 1000 ppm as compared to control. The results this study concluded that, Helianthus annuus L. was more respond of heavy metals, and after it comes Cucumis sativus L. while Lycopersion esculentum L. were the most sensitive.